BUSINESS PLAN 2017-2019 Tree Nuts: A New Business Unit for Packing San Javier - Morgan Bascuñan, Martin Felipe (2016)
The directors and owners of Packing San Javier (PSJ) are invited to review a new business unit for the following seasons.